Analysis of Eco-label and Natural Skincare Branding Strategy "Sensatia Botanicals" in Building Brand Awareness through Social Media - Hani Pritananda Anisasiwi; Fitrinanda An Nur (Jogjakarta Communication Conference (JCC), 2024)
This study aims to determine the strategies used by Sensatia Botanicals in building brand awareness among consumers and potential customers. The research discusses how the Eco-label Branding Strategy Analysis and Natural Skincare Sensatia Botanicals in Building Brand Awareness through Social Media. The method used in this study is qualitative descriptive by analyzing the content uploaded by Sensatia on its social media accounts, namely Tiktok and Instagram and conducting a literature study study. The results of this study show that branding carried out through social media platforms with efforts to create interesting, informative, and educational content to introduce their products made from natural and environmentally friendly raw materials becomes more value in the eyes of consumers or potential consumers from the content has succeeded in increasing brand awareness which has positive results in building awareness to be better known by the wider community from various circles Both women and men as quality local beauty care brands and have a commitment to care for the environment.